2012
DOI: 10.4304/jltr.3.4.716-721
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dictogloss Technique on Learners’ Writing Improvement in Terms of Writing Coherent Texts

Abstract: Abstract-Considering the communicative framework of language teaching, writing has an advantage-a person can give a variety of information to a close or distant, known or unknown reader or readers. Such way of communicating is highly important in the modern world, whether the communication is in the form of paper-and-pencil writing or advanced electronic writing. Therefore, this skill should be encouraged and nurtured during the language teaching course. Writing consists of different aspects like outline, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Iranian EFL learners face with many problems in English writing. Furthermore, in the context of task-based language teaching, 7(1):184-192 numerous studies have been carried out and the present study was evoked by many research studies on the field of focus on form, the importance of using task-based assessment (Namazi, 2007), the effect of structured-input instruction and out-put based instruction (Erlam, 2003),DIG task as an output based-task (Kooshafar, Youhanaee & Amirian, 2012;Kim, 2008;Kuiken & Vedder, 2002a;Swain, 1998;Swain, 2000;Swain & Lapkin, 2001) and CR task as an input based-task (Takimoto, 2009, Fotos, 1994Fotos & Ellis,1991) which signify the prominent role of tasks in language learning.…”
Section: Discussionmentioning
confidence: 99%
“…Iranian EFL learners face with many problems in English writing. Furthermore, in the context of task-based language teaching, 7(1):184-192 numerous studies have been carried out and the present study was evoked by many research studies on the field of focus on form, the importance of using task-based assessment (Namazi, 2007), the effect of structured-input instruction and out-put based instruction (Erlam, 2003),DIG task as an output based-task (Kooshafar, Youhanaee & Amirian, 2012;Kim, 2008;Kuiken & Vedder, 2002a;Swain, 1998;Swain, 2000;Swain & Lapkin, 2001) and CR task as an input based-task (Takimoto, 2009, Fotos, 1994Fotos & Ellis,1991) which signify the prominent role of tasks in language learning.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Nabei (1996) reported positive DG effects on female Polish and Chinese ESL learners' language skills. Similarly, Abbasian and Mohammadi (2013), Kooshafar et al (2012), Prince (2013), Purwaningsih & Kurniasih (2014), and Zheng (2006) reported that DG positively affects the written performance of Iranian, French, Nigerian and Chinese EFL learners, respectively. In the same vein, Khoii and Pourhassan (2015) have reported a positive effect of DG on Iranian EFL learners' immediate and delayed grammatical performance.…”
Section: Analysis and Correctionmentioning
confidence: 99%
“…A good body of local and international research exists on the effect of dictogloss on language learning (e.g., Abbasian & Mohammadi, 2013;Han, 2011;Nabei, 1996;Khoii & Pourhassan, 2015;Kooshafar et al, 2012;Prince, 2013;Purwaningsih & Kurniasih, 2014;Qin, 2008;Uludag & Vanpatten, 2012). However, to the best of these researchers' knowledge, other than a lone study by them (Bataineh & Bani Younis, 2016), none exists on the effect of DG-based training on teacher writing instruction and student written performance.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, over the last three or so decades, various problems in students' academic writing have been pointed out across different research contexts. For instance, grammatical inaccuracy and fossilization of linguistic errors (Mardijono, 2003;Myles, 2002), problems of coherence and cohesion (Kooshafar et al, 2012), lack of critically deliberated and well-supported arguments, lack of use of appropriate register and style (Ozarska, 2008), lack of use of appropriate genre, citation and referencing problems (Neville, 2007), and so on were claimed to be profound both in their frequency in and impact on the quality of students' writing.…”
mentioning
confidence: 99%